J-Lo’s Story: Can the Diva and the Genius Co-Exist? - Melissa Arlen Blank (Networks: An Online Journal for Teacher Research, 2008)
It was an average March day in Arizona. J-Lo sat in Algebra class, wearing her favorite Baby Girl t-shirt and a pair of jeans. She and her friend Clara were tipsy from sipping on a Gatorade bottle filled with a clever mix of Lemon-Lime tastiness and vodka. But J-Lo’s behavior wasn’t so clever. She decided to interject her daily commentary on the day’s lesson. “Mr. A, this class is so boring!” He noticed that she slurred her speech and seemed more disconnected than usual. One whiff of her potent concoction, and the teacher knew right away why J-Lo seemed to be on another planet. The teacher quickly called security and passed over the incriminating Gatorade bottle. But the next day to the disdain of her teacher, JLo loudly bounced into class with a wicked smile, boldly declaring a moral victory over an inferior administration. J-Lo was a smooth talker. Despite the fact that this incident really did happen, I can’t say that J-Lo is unintelligent. In fact, Jennifer “J-Lo” Lorenzo is an Honors student in my Geometry class at North High School and happens to be of Mexican descent.